(3GdCQL aj GdaQLs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdMQef GdQMje hGdMeO ddg QH GdYGdejf gPG JCdja dWja dNUJ ajg cJGH GdaQL HYO GdTOI dCHi HcQ GHf CHj GdOfjG eY RjGOGJ MSfg SejJg HGdCQL ai GdaQL hCaVd GdYHGOGJ EfJXGQ GdaQL s
(3BNQgG (B:s
(3GdMeO ddg GdPi dG jfSi ef PcQg hdG jNjH ef OYGg aQCi GdfHi Udi Gddg Ydjg hSde jG MSf cja CfJ bdJ HNjQ HQShd Gddg hMOKJg MOjKi abGd gcPG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs